The International Encyclopedia of Media Psychology 2020
DOI: 10.1002/9781119011071.iemp0121
|View full text |Cite
|
Sign up to set email alerts
|

Limited Capacity Model of Motivated Mediated Message Processing

Abstract: The limited capacity model of motivated mediated message processing (LC4MP) is a model for understanding the dynamic interactions between mediated messages and the human information processing system. At the time of its original writing, the LC4MP was unique in the landscape of media psychology research in that it eschewed rote investigation of message effects and instead focused on investigating how message structure and content interact with and influence various biological systems of the brain and body. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, studies have reported safety concerns related to Pokémon GO gameplay, such as traffic violations, trespassing, and other risky behaviors [ 43 ]. These concerns may stem from a lack of situational awareness and impaired decision-making as players become immersed in the game, consistent with the Limited Capacity Model of Motivated Mediated Message Processing [ 44 ]. The model suggests that when cognitive resources are devoted to gameplay, individuals may have a reduced capacity to process and respond to real-world environmental cues, increasing the likelihood of engaging in risky behaviors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have reported safety concerns related to Pokémon GO gameplay, such as traffic violations, trespassing, and other risky behaviors [ 43 ]. These concerns may stem from a lack of situational awareness and impaired decision-making as players become immersed in the game, consistent with the Limited Capacity Model of Motivated Mediated Message Processing [ 44 ]. The model suggests that when cognitive resources are devoted to gameplay, individuals may have a reduced capacity to process and respond to real-world environmental cues, increasing the likelihood of engaging in risky behaviors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns may stem from a lack of situational awareness and impaired decision-making as players become immersed in the game, consistent with the Limited Capacity Model of Motivated Mediated Message Processing [ 44 ]. The model suggests that when cognitive resources are devoted to gameplay, individuals may have a reduced capacity to process and respond to real-world environmental cues, increasing the likelihood of engaging in risky behaviors [ 44 ]. Therefore, it is crucial to promote responsible gameplay and parental supervision, emphasizing the importance of balancing digital activities with other essential aspects of life and ensuring that Pokémon GO and similar games do not adversely affect the health and safety of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Of the components of LC4MP, three are most relevant to this study: people have limited processing capacity; people process information in order to survive and thrive in an uncertain world; and mediated and non-mediated communication is processed in a similar fashion (Fisher & Weber, 2020;Pavolik, 2015;Fulton, 2014). While the limitations of working memory can limit what is successfully processed into long-term memory, the capacity of long-term memory is notably greater than working memory.…”
Section: Information Processing: the Limited Capacity Model For Motiv...mentioning
confidence: 99%